Bagaimana Membuat Komunitas Usia Lanjut Puas dengan Edukasi Kesehatan dan Konsultasi Kesehatan oleh Dokter Layanan Primer? Hal yang Dipelajari dari Program Kesehatan Bank Pensiunan - Aria Kekalih; Idqan Fahmi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction: Health education program to recognize and prevent degenerating disease is important for elderly. therefore, a national pension bank in Indonesia set initiative to provide health empowerment program in their waiting room, to optimize momentum when elderly community come and gather regularly in pension bank at every first week of the month. The bank organized health education and medical consultation program in the waiting room, cooperated with trained health educator and physician. This study investigated how elderly satisfy with the programs, and its effect to program and institution image. Method: We investigated 438 elderlies in 10 cities of 14 pension bank branches in Indonesia who participated in health education and consultation program. We assessed their satisfaction level related to health education and its cause using SERVQUAL approaches that consist of tangible, reliability, responsiveness, assurance and empathy. We also investigated how it would trigger individual willingness to spread word of mouth in promoting the health education program and the institution to other elderly, using standardized equation modeling (SEM) analysis. Result: Most of elderly satisfy and understood the both health education content (90%) and considered this program as meaningful program (84%). In health education, the highest factor contributes to elderly satisfaction were tangibles (educator and doctor performance) and reliability factors (regular schedule and delivery method of health education content). Meanwhile in medical consultation, doctor’s performance (tangible factor), responsiveness and empathy to elderly health problem contributed equally important to elderly satisfaction. Medical consultation contributed more in triggering word of mouth to promote the program and institution (SEM r=0.81) rather than of health education (SEM r=0.58)Conclusion: Not only doctor’s performance and health content delivery method, but responsiveness and empathy were important key factors to provide successful health education and services for elderly. Elderlies highly appreciated pension bank’s initiative in providing health education and consultation while optimizing time in waiting room, therefore this model can be applied in further health education program.